Efficient repeated batch production of androstenedione using untreated cane molasses by Mycobacterium neoaurum driven by ATP futile cycle. (August 2020) - Zhou, Xiuling; Zhang, Yang; Shen, Yanbing; Zhang, Xiao; Zan, Zehui; Xia, Menglei; Luo, Jianmei; Wang, Min
Highlights: Construction of ATP futile cycle (AFC) in mycobacteria for the first time. Application of AFCs reduced intracellular ATP and propionyl-CoA levels. Application of AFCs increased cell viability and key enzymes transcriptional level. The enhancement of propionyl-CoA metabolism and AFC has a synergistic effect. AD productivity increased by 181% through repeated batch fermentation. Abstract: The biotransformation of phytosterol to androstenedione (AD) by mycobacteria is a unique process accompanied by energy-producing. However, high intracellular ATP content can severely inhibit the efficient production of AD. In this study, a novel citrate-based ATP futile cycle (AFC) and pyruvate-based AFC were constructed for the first time. Application of AFCs reduced intracellular ATP and propionyl-CoA levels and increased NAD + /NADH ratios and cell viability. The forced consumption of ATP promotes the transcription of critical genes in propionyl-CoA metabolism. The synergistic effect of enhanced propionyl-CoA metabolism and AFC increased AD conversion yield from 60.6% to 97.3%. The AD productivity was further improved by repeated batch fermentation using untreated cane molasses. The maximum productivity was 181% higher than that of the original strain. Therefore, the strategy of combining AFC and repeated batch fermentation is a valuable tool for the efficient and low-cost production of AD and other steroidal pharmaceutical precursors.